Significant OH production under surface cleaning and air cleaning conditions: Impact on indoor air quality. (1st June 2017) - Carslaw, N.; Fletcher, L.; Heard, D.; Ingham, T.; Walker, H.
Abstract: We report measurements of hydroxyl (OH) and hydroperoxy (HO2 ) radicals made by laser‐induced fluorescence spectroscopy in a computer classroom (i) in the absence of indoor activities (ii) during desk cleaning with a limonene‐containing cleaner (iii) during operation of a commercially available "air cleaning" device. In the unmanipulated environment, the one‐minute averaged OH concentration remained close to or below the limit of detection (6.5×10 5 molecule cm −3 ), whilst that of HO2 was 1.3×10 7 molecule cm −3 . These concentrations increased to 4×10 6 and 4×10 8 molecule cm −3, respectively during desk cleaning. During operation of the air cleaning device, OH and HO2 concentrations reached 2×10 7 and 6×10 8 molecule cm −3 respectively. The potential of these OH concentrations to initiate chemical processing is explored using a detailed chemical model for indoor air (the INDCM). The model can reproduce the measured OH and HO2 concentrations to within 50% and often within a few % and demonstrates that the resulting secondary chemistry varies with the cleaning activity. Whilst terpene reaction products dominate the product composition following surface cleaning, those from aromatics and other VOCs are much more important during the use of the air cleaning device.